EFEKTIVITAS MENGKONSUMSI BUAH NANAS (ANANAS COMOSUS) DAN BUAH BELIMBING (AVERRHOA CARAMBOLA L) TERHADAP SKOR PLAK - Irmanita Wiradona; Prasko Prasko (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2018)
TITLEEFFECTIVENESS CONSUMING PINEAPPLE (ANANAS COMOSUS) AND STAR FRUIT (AVERRHOA CARAMBOLA L) TOWARD PLAQUE SCOREABSTRACTPineapple and Star fruit are one of the fruits that has water content and fiber that many. Pineapple sources of vitamin C and manganese, this fruit also contains substances that can maintain bone strength and help digestion. Fresh fruit contains 10% sugar, half is the remaining sucrose glucose and fructose. Pineapple fruit rich in fiber can reliably increase saliva production (saliva), clean teeth and mouth and strengthen the gums. While starfruit contains epitekin compounds that are bactericidal. Research purposes this is to know the effectiveness of pineapple and star fruit consumption toward plaque score.This research is an experimental research with the design of Pre and Post Test Group Design. The sample of this research is MI Darut Taqwa Meteseh, Tembang, Semarang as many as 60 students divided by 4 intervention groups. Interventions taken are consuming star fruit juice, pineapple juice, chewing starfruit and pineapple. Dental plaque scores were measured using the index PHP. Data analysis using a t-test.The research result from score plaque drink juice star fruit and chew starfruit with p = 0,001 so there is the difference of plaque score between drinking star fruit juice by chewing star fruit. Score plaque group who drank pineapple juice and chewed pineapple with p = 0.017 so there was a difference in plaque score between drinking pineapple juice by chewing pineapple. Consume fruit by chewing more down the plaque score compared to drinking fruit juice. Consume pineapple lower plaque than consuming star fruit. Keywords : starfruit, pineapple fruit, plaque score.___________________________________________________________1,2) Jurusan Keperawatan Gigi Poltekkes Kemenkes Semarang * : irmanita.wiradona@gmail.com